Role of histopathology in predicting type 1 lepra reaction in borderline tuberculoid leprosy - Dhanya Sankaran; Sarita Sasidharanpillai; Kidangazhiyathmana Ajithkumar; Aparna Govindan; Ekkila Valappil Seemi; Puthen Parambath Sathi (Wolters Kluwer Medknow Publications, 2020)
Context: Lepra reactions if not managed promptly are an important cause of sudden onset nerve palsy and disability due to leprosy. Aim: To evaluate the usefulness of histology in predicting type 1 lepra reaction. Setting and Design: After obtaining clearance from institutional research and ethics committees, all histologically proven borderline tuberculoid patients diagnosed at our center from 1.8.2016 to 31.7.2018 were included in this retrospective cross-sectional study. Method: Clinical details were collected from patient records. The pathologist who was blinded to clinical evidence of type 1 lepra reaction at the time of biopsy re-evaluated the histopathology slides for evidence of type 1 reaction. The data of individual patient was analyzed to identify those who had a type 1 reaction at the time of the biopsy or who developed a lepra reaction during follow up. Statistical Analysis Used: Association between histological evidence of type 1 reaction and clinical manifestation of the same subsequently, was assessed using Pearson's Chi square test. Results: Study group comprised of 22 females and 18 males. Clinicohistological concordance was noted in 27 patients (67.5%). Subclinical type 1 reaction was documented in 11 patients (27.5%) based on histopathology evaluation. Five (45.5%) of these 11 patients subsequently developed clinical features of type 1 reaction. This was found to be statistically significant (P value 0.02). Limitations: Main limitation was the small sample size. Conclusions: Histology could serve as a useful tool in predicting future type 1 lepra reaction.